(untitled) (Plant Tissue Culture and Biotechnology, 2017)
The effects of genotype, explant source and basal media on shoot growth and callus formation of the mature explants of Camellia japonica and Hydrangea macrophyla were studied. Apical and lateral buds showed higher growth potential compared to meristem in the both species. The best results in three cultivars of C. japonica were obtained on WPM supplemented with 2 mg/l TDZ + 0.5 mg/l Kn + 1 mg/l GA3. Similarly, best result was observed in two cultivars of H. macrophylla on MS supplemented with 1 mg/l BAP + 0.1 mg/l NAA + 1 mg/l GA3. Plant Tissue Cult. & Biotech. 27(2): 181-187, 2017 (December)